Parasites of Trinidadian guppies: evidence for sex‐ and age‐specific trait‐mediated indirect effects of predators - Jessica F. Stephenson; Cock van Oosterhout; Ryan S. Mohammed; Joanne Cable (Ecology, 2015)
Predation pressure can alter the morphology, physiology, life history, and behavior of prey; each of these in turn can change how surviving prey interact with parasites. These trait‐mediated indirect effects may change in direction or intensity during growth or, in sexually dimorphic species, between the sexes. The Trinidadian guppy, Poecilia reticulata presents a unique opportunity to examine these interactions; its behavioral ecology has been intensively studied in wild populations with well‐characterized predator faunas. Predation pressure is known to have driven the evolution of many guppy traits; for example, in high‐predation sites, females (but not males) tend to shoal, and this anti‐predator behavior facilitates parasite transmission. To test for evidence of predator‐driven differences in infection in natural populations, we collected 4715 guppies from 62 sites across Trinidad between 2003 and 2009 and screened them for ectosymbionts, including Gyrodactylus . A novel model‐averaging analysis revealed that females were more likely to be infected with Gyrodactylus parasites than males, but only in populations with both high predation pressure and high infection prevalence. We propose that the difference in shoaling tendency between the sexes could explain the observed difference in infection prevalence between males and females in high‐predation sites. The infection rate of juveniles did not vary with predation regime, probably because juveniles face constant predation pressure from conspecific adults and therefore tend to shoal in both high‐ and low‐predation sites. This represents the first evidence for age‐ and sex‐specific trait‐mediated indirect effects of predators on the probability of infection in their prey.

Antecedent Conditions Influence Soil Respiration Differences in Shrub and Grass Patches - Jessica M. Cable; Kiona Ogle; Greg A. Barron-Gafford; Lisa P. Bentley; William L. Cable; Russell L. Scott; David G. Williams; Travis E. Huxman (Ecosystems, 2013)

Woody plant encroachment impacts on soil carbon and microbial processes: results from a hierarchical Bayesian analysis of soil incubation data - Jessica M. Cable; Kiona Ogle; Anna P. Tyler; Mitchell A. Pavao-Zuckerman; Travis E. Huxman (Plant and Soil, 2009)

Soil Texture Drives Responses of Soil Respiration to Precipitation Pulses in the Sonoran Desert: Implications for Climate Change - Jessica M. Cable; Kiona Ogle; David G. Williams; Jake F. Weltzin; Travis E. Huxman (Ecosystems, 2008)

Effects of an increase in summer precipitation on leaf, soil, and ecosystem fluxes of CO2 and H2O in a sotol grassland in Big Bend National Park, Texas - Lisa Patrick; Jessica Cable; Daniel Potts; Danielle Ignace; Greg Barron-Gafford; Alden Griffith; Holly Alpert; Natasja Van Gestel; Traesha Robertson; Travis E. Huxman; John Zak; Michael E. Loik; et al. (Oecologia, 2007)

Response of net ecosystem gas exchange to a simulated precipitation pulse in a semi-arid grassland: the role of native versus non-native grasses and soil texture - Travis E. Huxman; Jessica M. Cable; Danielle D. Ignace; J. Alex Eilts; Nathan B. English; Jake Weltzin; David G. Williams (Oecologia, 2004)

Precipitation pulse size effects on Sonoran Desert soil microbial crusts - Jessica M. Cable; Travis E. Huxman (Oecologia, 2004)